2014
DOI: 10.1098/rspa.2014.0014
|View full text |Cite
|
Sign up to set email alerts
|

Scaling theory of electric-field-assisted tunnelling

Abstract: Recent experiments report the current (I) versus voltage (V) characteristics of a tunnel junction consisting of a metallic tip placed at a distance d from a planar electrode, d varying over six orders of magnitude, from few nanometres to few millimetres. In the ‘electric-field-assisted’ (or ‘field emission’) regime, as opposed to the direct tunnelling regime used in conventional scanning tunnelling microscopy, all I–V curves are found to collapse onto one single graph when d is suitably rescaled, suggesting th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The preset current value depends on the junction quality and can vary from 100 nA up to 400 nA. An exhaustive study of the tip-sample junction can be found in [3].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The preset current value depends on the junction quality and can vary from 100 nA up to 400 nA. An exhaustive study of the tip-sample junction can be found in [3].…”
Section: Methodsmentioning
confidence: 99%
“…To this end, we revisited the Russel Young topografiner [2]. We dubbed this new technique Near Field-Emission Scanning Electron Microscopy (NFESEM) [3], [4]. In NFESEM low-energy electrons are emitted from a polycrystalline tungsten tip via electric-field-assisted tunneling.…”
Section: Introductionmentioning
confidence: 99%